An Analysis of Implementation Taqlid Learning Methods in Intensive Class 1 Mahfudzot Lessons B Kulliyatu-L Mu'alimat Al-Islamiyah (Kmi - Haqiqi, Nurul Azizah; Jaenullah, Jaenullah; Pratiwi, Wiwied (Sekolah Tinggi Agama Islam Al-Furqan, Makassar - Indonesia, 2025)
Islamic This research examines the application of the Taqlid method in teaching Mahfudzot to female students in class 1 Intensive B at KMI Pondok Modern Darussalam Gontor Putri 8. This method emphasizes repetition and imitation, where female students imitate the teacher's pronunciation directly before understanding the meaning in depth. The learning stages include conveying vocabulary, explaining the material, and repeating verses until the students are able to memorize them well. The research results show that the Taqlid method has a number of advantages, such as making the memorization process easier, increasing understanding, and fostering enthusiasm for learning. However, this method also faces obstacles, such as limited time, difficulty in maintaining student concentration, and problems such as feeling sleepy during learning. However, the Taqlid method has proven effective in helping female students master Mahfudzot, an important subject that contains advice and moral values. This research emphasizes the importance of structured teaching strategies and the need for solutions to overcome obstacles in implementing this method. With optimization, the Taqlid method can be an effective approach to improving learning outcomes, character formation and academic readiness of female students.